PP-021 Ready-to-use medicines safety?! national evaluation of standardised drug solutions in the intensive care medicine. (24th March 2015) - Manske, M; Eisert, A; Baehr, M; Kluge, S; Hilgarth, H; Langebrake, C
Abstract : Background: Ready-to-use drug-solutions for syringe pumps produced by industry or hospital pharmacies have advantages over solutions prepared manually on the ward in terms of accuracy of drug concentration and microbiological aspects. A key prerequisite for large-scale productions is to standardise concentrations, as treatment varies at the local level. Purpose: To assess the different concentrations that are being used in intensive care units nationally and the variety of ready-to-use solutions that are being manufactured by hospital pharmacists. Material and methods: Two surveys were conducted among the hospital pharmacies and intensive care units (ICU) in the national university hospitals. The answers were evaluated descriptively. Results: Overall 100 different drugs were used in 262 different locally-standardised concentrations in the responding 17 hospitals. Of those, only 21 drugs were mentioned by at least two thirds of the ICUs: e.g. catecholamines, hypnotics, insulin, heparin, hydrocortisone and amiodarone. Among the 24 different drugs prepared by the responding 19 hospital pharmacies, the main ones reported were expensive drugs and/or preparations that are extremely prone to error (argatroban, caspofungin). There was only a little overlap (n = 6) between the standardised drugs used in the ICU and the hospital pharmacy-based manufacturing of ready-to-use preparations. Out of these only potassium chloride and heparin were being manufactured by at least five pharmacies. Conclusion: The observed gap might be due to limited manufacturing capacities of the pharmacies and/or limited stability data of the ready-to-use preparations (concentration, diluent and primary container). Standardising the drug concentrations on a national, or even European level might enable hospital pharmacies to cooperate in overcoming the lack of stability data. The capacity deficit at the hospital pharmacies could be lessened by shifting high-turnover-drugs towards pharmaceutical companies. For nationwide recommendations of standardised concentrations of drugs used in intensive care an extensive survey among ICUs is being planned. References and/or acknowledgements: No conflict of interest.